Kekuatan transversa resin akrilik hybrid setelah penambahan glass fiber dengan metode berbeda (The transverse strength of the hybrid acrylic resin after glass fiber reinforcement with different method) - Intan Nirwana (Dental Journal (Majalah Kedokteran Gigi), 2005)
Different types of fibers have been added to acrylic resin materials to improve their mechanical properties. The purpose of this study was to know the transverse strength of the hybrid acrylic resins after glass fiber reinforcement with difference method. This study used rectangular specimens of 65 mm in length, 10 mm in width and 2.5 mm in thickness. There were 3 groups consisting of 6 specimens each, hybrid acrylic resin without glass fiber (control), glass fibers dipped in methyl methacrylate monomer for 15 minutes before being reinforced into hybrid acrylic resin (first method), glass fibers reinforced into a mixture of polymer powder and monomer liquid after the hybrid acrylic resin was mixed directly (second method). All of the specimens were cured for 20 minutes at 100° C. Transverse strength was measured using Autograph. The statistical analyses using one way ANOVA and LSD test showed that there were significant differences in transverse strength (p < 0.05) among the groups. The means of transverse strength were 94,94; 118,27; and 116,34 MPa. It meant that glass fibers reinforcement into hybrid acrylic resin enhanced their transverse strength compared with control. Glass fiber reinforcement into hybrid acrylic resin with differenciate method didn’t enhance their transverse strength.